ADOPTING DATA ANALYTICS IN AUDITING: A STUDY OF INTERNAL AUDITORS AT MALAYSIA’S FINANCIAL INSTITUTION - Rafeah Mat Saat; Hannan Zamilah Hamdi; Raudah Danila, (ADVANCED INTERNATIONAL JOURNAL OF BANKING, ACCOUNTING AND FINANCE (AIJBAF), 2025)
The rapid advancement of technology has significantly impacted the auditing profession, highlighting the need for IT-savvy auditors who can leverage tools such as data analytics to enhance audit procedures. This study examines the factors influencing the adoption of data analytics among internal auditors at a financial institution in Malaysia. Utilizing the Unified Theory of Acceptance and Use of Technology (UTAUT) and IT Competency theory, this research explores the relationship between performance expectancy, effort expectancy, social influence, facilitating conditions, and IT skills with the intention to use data analytics. Additionally, it investigates facilitating conditions, IT skills, and intention to use influence the actual usage of data analytics. Data were collected through an online survey of 72 internal auditors from the financial institution’s internal audit department and analysed using SmartPLS. The results indicate that performance expectancy, social influence, and facilitating conditions positively and significantly influence the intention to use data analytics, while effort expectancy does not. Moreover, both IT skills and intention to use significantly impact the actual usage of data analytics. This study provides valuable theoretical and practical insights, validating the applicability of UTAUT and IT Competency theory in this context and offering a deeper understanding of internal auditors' perceptions of data analytics in audit procedures.